The Impact of Duration of Type 2 Diabetes Mellitus on Retina and Overall Eye Health in Pakistan’s Population (Medical Forum Monthly, 2024)
Objective: With reference to the study conducted in Pakistan, the following hypotheses were postulated with the view to establish relationship between the longevity of T2DM and retina health; moreover, to establish factors that affects its progression over time.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Mehboob Charity Vision International Eye and General Hospital in Mansehra from May 2023 to January 2024.Methods: This study examines 420 diabetic patients from Mehboob Charity Vision International Eye and General Hospital in Mansehra, Pakistan, diagnosed with type 2 diabetes for at least five years. The sample was diverse, representing both genders and ethnic backgrounds, and was selected using a simple random sampling procedure.Results: A study conducted on 3865 patients with diabetes, focusing on their demographics, sociodemographic, and diabetes-related data. The majority of participants were male and female, with a majority residing in rural areas. The majority of patients had Type 1 diabetes, with 90.75% (n=380) having the condition. The study revealed varying familial contexts, with 31.90% (n=134) having no diabetes history and 8.58% (n=36) having a family history from both parents. The majority of patients had uncontrolled blood sugar levels and hypertension. The duration of diabetes was found to be between 1-5 years, with most diagnosed within the last 1-5 years. Discomfort levels decreased with diabetes duration, and mild non-proliferative diabetic retinopathy (NPDR) and proliferative diabetic retinopathy (PDR) cases decreased. The study suggests a potential decline in visual acuity functions in later years, particularly in terms of perception of light, hand movement, and counting figures. Hence, suggesting the higher complications in first 10 years of diabetic duration.Conclusion: Diabetes duration is a threat to eyes as the 1-10 years group complained of more complications. Because diabetic retinopathy and cataracts relate to long-term glucose control, sustained measures are necessary to prevent or cure the illnesses.